Restless Legs Syndrome in Pediatric Patients With Nephrotic Syndrome - Victoria Cheung BA; Sara Wertenteil; Susan Sasson; Suzanne Vento RN; Sanjeev Kothare MD; Howard Trachtman MD (SAGE Publishing, 2015)
Background . Restless legs syndrome (RLS) is a sleep disorder characterized by an urge to move or the presence of unpleasant sensations in the extremities. The prevalence of RLS is higher in children and adults with chronic kidney disease and in adults with glomerular disease. Objective . To determine the prevalence of RLS in children with nephrotic syndrome. Methods . We studied 50 children with nephrotic syndrome and 22 controls. The following surveys were administered: Pediatric Emory RLS questionnaire, Pediatric Daytime Sleepiness Scale, and Pediatric Sleep Questionnaire. Results . Children with nephrotic syndrome were 9.0 ± 4.4 years old, 27 were male, and 27 were in remission. The prevalence of RLS was similar in the nephrotic syndrome cases and controls, whether or not indeterminate cases were considered positive: 14.0% versus 13.6% including indeterminate cases, and 8.0% versus 9.1% excluding indeterminate cases. Conclusion . RLS is not more common in children with glomerular disease compared to healthy controls.